2008
DOI: 10.1186/1472-6939-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of a research ethics training workshop among clinicians and scientists in a Nigerian university

Abstract: Background: In Nigeria, as in other developing countries, access to training in research ethics is limited, due to weak social, economic, and health infrastructure. The project described in this article was designed to develop the capacity of academic staff of the College of Medicine, University of Ibadan, Nigeria to conduct ethically acceptable research involving human participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 8 publications
7
55
0
Order By: Relevance
“…Short training programs in ethics have been shown effective in various studies at different contexts [6,7,11]. Our findings also support this and found that the short training programs are effective.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Short training programs in ethics have been shown effective in various studies at different contexts [6,7,11]. Our findings also support this and found that the short training programs are effective.…”
Section: Discussionsupporting
confidence: 81%
“…Similar observations were made by Ajuwon and Kass in Ethiopia in a qualitative research which showed the effectiveness of a research ethics workshop among students and faculty. In this study the investigators organized three rounds of workshop each session lasting 7h using various methods such as group work, case studies and lectures which showed a significant increase in Knowledge, Attitude and Skills towards research ethics among faculty following a workshop [6]. Similar observations were made by Barchi et al, in their randomised control study on two groups of researchers in Botswana in building research capacity showed the effectiveness of short training programs.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Combining small group learning, practical cases, role-play and interdisciplinary learning have also been reported as effective approaches to providing education in research ethics (Zawati et al 2015). Similarly, programs reported to improve capacity in research supervision have included short courses, workshops or specific training (Balster et al 2010;Ramalingam et al 2014;Ajuwon and Kass 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ajuwon and Kass at Ibadan, South-Western Nigeria, showed that there is a gap in knowledge among researchers about the principles of ethics in clinical research [17]. We therefore sought to assess the knowledge of resident doctors at LASUTH on ethical issues and the operations of the ethics committee.…”
mentioning
confidence: 99%